Interface - Hookway, Branden (The MIT Press, 2014)
"In this book, Branden Hookway considers the interface not as technology but as a form of relationship with technology. The interface, Hookway proposes, is at once ubiquitous and hidden from view. It is both the bottleneck through which our relationship to technology must pass and a productive encounter embedded within the use of technology. It is a site of contestation--between human and machine,between the material and the social, between political and the technological -- that both defines and elides differences." -- Provided by publisher